Evaluation of the Efficacy of a Bacteriophage in the Treatment of Pneumonia Induced by Multidrug Resistance Klebsiella pneumoniae in Mice. (23rd March 2015) - Cao, Fang; Wang, Xitao; Wang, Linhui; Li, Zhen; Che, Jian; Wang, Lili; Li, Xiaoyu; Cao, Zhenhui; Zhang, Jiancheng; Jin, Liji; Xu, Yongping
Abstract : Multidrug-resistant Klebsiella pneumoniae (MRKP) has steadily grown beyond antibiotic control. However, a bacteriophage is considered to be a potential antibiotic alternative for treating bacterial infections. In this study, a lytic bacteriophage, phage 1513, was isolated using a clinical MRKP isolate KP 1513 as the host and was characterized. It produced a clear plaque with a halo and was classified as Siphoviridae. It had a short latent period of 30 min, a burst size of 264 and could inhibit KP 1513 growth in vitro with a dose-dependent pattern. Intranasal administration of a single dose of 2 × 10 9  PFU/mouse 2 h after KP 1513 inoculation was able to protect mice against lethal pneumonia. In a sublethal pneumonia model, phage-treated mice exhibited a lower level of K. pneumoniae burden in the lungs as compared to the untreated control. These mice lost less body weight and exhibited lower levels of inflammatory cytokines in their lungs. Lung lesion conditions were obviously improved by phage therapy. Therefore, phage 1513 has a great effect in vitro and in vivo, which has potential to be used as an alternative to an antibiotic treatment of pneumonia that is caused by the multidrug-resistant K. pneumoniae .